Mathematical Problem-Solving Skills in View of Self-Efficacy in GeoGebra-Assisted Project-Based Learning - Rahmawati, Laila; Walid, Walid; Cahyono, Adi Nur (JURNAL PENDIDIKAN MATEMATIKA, 2025)
The research aims to analyze the effectiveness of a project-based learning model assisted by GeoGebra on mathematical problem-solving skills and analyze mathematical problem-solving skills in terms of self-efficacy. The research used a mixed method sequential explanatory design with a pretest-posttest control group design. Sample selection using cluster random sampling. Class VIIIA had 31 students as the experimental class, and class VIIIB had 30 as the control class. Data collection used a self-efficacy questionnaire, interviews, and tests. Quantitative data analysis used the average completeness test, proportion test, mean difference test, proportion difference test, and n-gain test with the help of Rstudio. Data collection, reduction, presentation, and conclusions to analyze qualitative data. The results of the research found that the project-based learning model assisted by GeoGebra was effective on mathematical problem-solving skills, subjects with high self-efficacy were able to fulfill four indicators of mathematical problem-solving skills, medium self-efficacy subjects were only not optimal in the indicator of applying various appropriate strategies to solve problems, and low self-efficacy subjects were only optimal in the indicator of building new mathematical knowledge through problem-solving and solving problems in mathematics or other contexts. Keywords: Mathematical Problem Solving, Project Based Learning, GeoGebra, Self Efficacy